2014
DOI: 10.1007/s10903-014-0014-y
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Religion-Related Factors and Breast Cancer Screening Among American Muslims

Abstract: American Muslims have low rates of mammography utilization, and research suggests that religious values influence their health-seeking behaviors. We assessed associations between religion-related factors and breast cancer screening in this population. A diverse group of Muslim women were recruited from mosques and Muslim organization sites in Greater Chicago to self-administer a survey incorporating measures of fatalism, religiosity, discrimination, and Islamic modesty. 254 surveys were collected of which 240 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
70
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 52 publications
10
70
2
1
Order By: Relevance
“…Informants' views about God's will and predetermination are consistent with other studies that focused on associations between religion and health (Padela et al, 2015). Overall our findings support that religion displays an influential role in the community's attitudes and perception toward genetics and genetic service delivery.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Informants' views about God's will and predetermination are consistent with other studies that focused on associations between religion and health (Padela et al, 2015). Overall our findings support that religion displays an influential role in the community's attitudes and perception toward genetics and genetic service delivery.…”
Section: Discussionsupporting
confidence: 89%
“…Some KIs indicated that the community has a knowledge gap about genetics and have anecdotal beliefs of associating health/genetic conditions to the Islamic faith rather than medical/scientific explanations. Informants’ views about God's will and predetermination are consistent with other studies that focused on associations between religion and health (Padela et al, ). Overall our findings support that religion displays an influential role in the community's attitudes and perception toward genetics and genetic service delivery.…”
Section: Discussionsupporting
confidence: 85%
“…Other studies exist that examined the link between religion or spirituality and health screening behavior [37][38][39][40][41][42][43][44][45][46] as well as mental health service utilization. [47][48][49] These studies mainly showed that these explanatory variables were associated with greater use of preventive care services, whereas they were associated with decreased utilization of professional mental health services.…”
Section: Discussionmentioning
confidence: 99%
“…Scoring on this scale would allow public health authorities in the country to incorporate the awareness that the disease is likely to be treated and possibly cured if detected in a timely manner (Padela et al, 2015), since fatalism forms part of the most rigid system in the enabling systems model. Several studies have found that culturally-sensitive breast cancer education programmes can have a significant impact on changing knowledge and beliefs about breast cancer (Hall et al, 2005;Bickell et al, 2009).…”
Section: Discussionmentioning
confidence: 99%